Lifestyle factors, serum parameters, metabolic comorbidities, and the risk of kidney stones: a Mendelian randomization study - Liu, Minghui; Wu, Jian; Gao, Meng; Li, Yongchao; Xia, Weiping; Zhang, Youjie; Chen, Jinbo; Chen, Zhiyong; Zhu, Zewu; Chen, Hequn (Frontiers in Endocrinology, 2023)
Background and objective: Early identification of modifiable risk factors is important to prevent kidney stones, but determining causal association can be difficult in epidemiological data. We aimed to genetically assess the causality between modifiable factors (lifestyle factors, serum parameters and metabolic comorbidities) and the risk of kidney stones. Additionally, we aimed to explore the causal impact of education on kidney stones and its potential mediating pathways.We conducted a two-sample mendelian randomization (MR) study to explored the causal association between 44 modifiable risk factors and kidney stones. The FinnGen dataset was initially explored the causal relationship of risk factors with kidney stones and UK Biobank dataset was used as the validation set. Then a meta-analysis was conducted by combining discovery and validation datasets. We used two-step MR to assess potential mediators and their mediation proportions between education and kidney stones.The combined results indicated that previous exposures may increase the risk of kidney stones, including, sedentary behavior, urinary sodium, urinary sodium/potassium ratio, urinary sodium/creatinine ratio, serum calcium, 25-hydroxyvitamin D (25OHD), estimated creatinine-based glomerular filtration rate (eGFRcrea), GFR estimated by serum cystatin C (eGFRcys), body mass index (BMI), waist circumference, Type 2 Diabetes Mellitus (T2DM), fasting insulin, glycated hemoglobin and hypertension. Coffee intake, plasma caffeine levels, educational attainment and urinary potassium/creatinine ratio may decrease the risk of kidney stones. Ranked by mediation proportion, the effect of education on the risk of kidney stones was mediated by five modifiable risk factors, including sedentary behavior (mediation proportion: 25.7%), smoking initiation (10.2%), BMI (8.2%), T2DM (5.8%) and waist circumference (3.2%).This study provides MR evidence supporting causal associations of many modifiable risk factors with kidney stones. Sedentary lifestyles, obesity, smoking and T2DM are mediating factors in the causal relationship between educational attainment and kidney stones. Our results suggest more attention should be paid to these modifiable factors in order to prevent kidney stones.